Strategic design of a learning commons at Luleå University of Technology - Lundkvist, Peter; Sundlöf, Robert; Tanskanen, Seppo; Tiburzi, Markus (Luleå tekniska universitet, 2005)
There is a desire of changing libraries and librarians work procedures with the purpose to create a learning and knowledge creative environment for students. This environment is called The Learning Commons (LC). The idea is to enable students to manage their own learning within an environment designed to both prompt and facilitate the use of the full range of library resources assembled to support learning within colleges and universities. Therefore, a LC must be de-signed to handle these things. In this report we provide a design strategy for both the physical and virtual knowledge environment. Our research shows, among other things, that in the physical LC a café is important as it draws people to the LC and that within the virtual LC everything should be gathered in one place. Hence, you only log-in to one place. Another important finding is that roles and work procedures will change in many ways for the people involved in a LC. Godkänd; 2005; 20080522 (ysko)